Miíase por Lucilia eximia (Diptera: Calliphoridae) em Didelphis albiventris (Mammalia: Didelphidae) no Brasil Central - Cansi, Edison Rogerio; Bonorino, Rafael (EntomoBrasilis, 2011)
Em maio de 2009 foram coletadas 18 larvas de Lucilia eximia (Wiedemann), mosca responsável por miíases primárias e secundárias em animais domésticos e seres humanos. As larvas foram retiradas das regiões anal e auricular de um gambá, Didelphis albiventris (Lund), no Zoológico de Brasília, e posteriormente identificadas em laboratório. Após 15 dias emergiram 15 adultos de L. eximia. Este é o primeiro registro desta mosca causando miíase primária em um marsupial no Cerrado de Brasília. Myiasis by Lucilia eximia (Diptera: Calliphoridae) in Didelphis albiventris (Mammalia: Didelphidae) in Central Brazil Abstract. In May 2009 were collected 18 larvae of Lucilia eximia (Wiedemann), a fly responsible for primary and secondary myiasis in livestock and humans. The larvae were taken from the myiasis on anal and auricular regions of an opossum Didelphis albiventris (Lund), in Brasília Zoo, and later identified in the laboratory. After 15 days, 15 adults emerged from L. eximia. This is the first record of this blowfly causing a primary myiasis in a marsupial species in the Brasília Cerrado.